The Prospect of AI Law in Indonesian Legal System: Present and Future Challenges - Ardina Khoirun Nisa (The Indonesian Journal of International Clinical Legal Education, 2024)
The development of AI and its ease of use in cyberspace raises various legal problems. This situation is because AI can take actions that could potentially lead to illegal activities. Therefore, to overcome the problems that arise from the use of AI, legislation is needed to regulate it. This research aims to analyze the legal provisions for the use of AI in Indonesian Law. This research is qualitative research with a normative legal approach, and the data analysis method used is qualitative juridical. The results showed that the use of AI in the legal field has been widely carried out, including it can be used to predict case outcomes and make strategic recommendations. AI can also estimate the cost needed to solve cases. In addition, AI facilitates the development of rules and regulations and the creation of contracts. However, with the use of AI, the legal provisions governing it are considered insufficient. In addition to Statute Number 19 of 2016 Regarding Amendments to Statute Number 11 of 2008 Regarding Electronic Information and Transactions and Regulation of Government Number 71 of 2019 Regarding the Execution of Electronic Systems and Transactions, there must be new and specific regulations governing the use of artificial intelligence.